Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1074/jbc.m405874200
|View full text |Cite
|
Sign up to set email alerts
|

PSD-95 and Lin-7b Interact with Acid-sensing Ion Channel-3 and Have Opposite Effects on H+-gated Current

Abstract: The acid-sensing ion channel-3 (ASIC3) is a degenerin/ epithelial sodium channel expressed in the peripheral nervous system. Previous studies indicate that it participates in the response to mechanical and painful stimuli, perhaps contributing to mechanoreceptor and/or H ؉ -gated nociceptor function. ASIC3 subunits contain intracellular N and C termini that may control channel localization and function. We found that a PDZ-binding motif at the ASIC3 C terminus interacts with four different proteins that contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
53
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 48 publications
(61 reference statements)
12
53
0
1
Order By: Relevance
“…Rat ASIC3 in pMT3 vector was cloned as described previously (20). HA-ASIC3 was generated by insertion of two hemagglutinin (HA) epitopes (YPYDVPDYA-G-YPYDVPDYA) at the NH2 terminus of ASIC3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rat ASIC3 in pMT3 vector was cloned as described previously (20). HA-ASIC3 was generated by insertion of two hemagglutinin (HA) epitopes (YPYDVPDYA-G-YPYDVPDYA) at the NH2 terminus of ASIC3.…”
Section: Methodsmentioning
confidence: 99%
“…Knockdown of PSD-95 in rat spinal cord attenuated, and targeted disruption of PSD-95 in mice abolished, hyperalgesia to mechanical and thermal stimuli following nerve injury (15,43,44). Previously, work in our laboratory demonstrated that both PSD-95 and ASIC3 are present in dorsal root ganglia and coimmunoprecipitate together in rat spinal cord (20).PSD-95 is essential for normal synaptic plasticity at postsynaptic sites, where it integrates signaling by localizing and clustering proteins (26). PSD-95 forms multimers, and each subunit contains three PDZ domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although similar to glutamate receptors, they are also present on dendrites and cell bodies (20,(22)(23)(24). ASIC subunits interact with postsynaptic scaffolding proteins, including postsynaptic density protein 95 and protein interacting with C-kinase-1 (20,(24)(25)(26)(27)(28)(29). In addition, ASICs are enriched in synaptosome-containing brain fractions (20,24,30).…”
mentioning
confidence: 99%
“…The extracellular domain senses protons and interacts with modulators, including proteases, Zn 2ϩ , Ca 2ϩ , and redox reagents (42). The cytoplasmic NH 2 and COOH termini contain phosphorylation sites and interact with other proteins such as protein interacting with C kinase 1 (PICK1) (14,25,42), postsynaptic density protein 95, abnormal cell lineage 7b (24), and annexin (13), resulting in changes in the current density or cellular localization of ASIC. For example, PICK1 increases the ASIC2a current amplitude by potentiating the phosphorylation of ASIC2a at T39 [equivalent to site S40 on human (h)ASIC1b] (3).…”
mentioning
confidence: 99%